PENGUATAN KARAKTER REMAJA SMK MENJADI REMAJA KUATREMAJA HEBAT DI SMK MITRA TANI PANYABUNGAN - Harahap, Siti Rahma (Karsa : Jurnal Pengabdian Masyarakat, 2025)
Strengthening the character of vocational school youth to become strong and great teenagers is a youth seminar held at MITRA TANI Vocational School, Panyabungan. This seminar aims to empower youth to develop individuals with strong morals, good ethics, and superior personalities, thus becoming responsible, independent, and virtuous citizens. Social phenomena frequently occurring among adolescents, such as juvenile delinquency, brawls, alcohol and drug parties, promiscuity leading to promiscuity, and criminal acts such as robbery, murder, and many more, reflect youth who are not great and strong, and this has also become a concern for parents and the community. The seminar was attended by 50 vocational school students, consisting of members of the MITRA TANI Vocational School Student Council (OSIS), with speakers from universities and the police. With a one-day seminar, this activity was packaged using a service learning method, students were motivated to understand the meaning of the material presented by relating it to the context of everyday life. Specifically, on the occurrence of the phenomenon of adolescent cases and the causes and solutions provided, and provided an opportunity for students to ask questions and be answered by the speaker. The seminar on strengthening adolescents that was carried out resulted in vocational high school students realizing the importance of being a teenager with character. In addition, students also instilled in themselves the ability to be able to become great and strong teenagers. The contribution of this article provides knowledge about  trengthening the character of great and strong teenagers and can be used as a reference for deepening community service activities related to adolescent character. Keywords: Adolescent character education; vocational school youth; character strengthening; moral and ethical development; youth empowerment